Analysis of Cybersecurity Awareness Among Social Media Users Among Teenagers Using Exploratory Factor Analysis (EFA) & Confirmatory Factor Analysis (CFA) Methods - Angela, Sofia; Huda, Muhamat Maariful; Rusdiyan, Rizqi Darma (Journal of Electrical Engineering and Computer (JEECOM), 2025)
Nowadays, security awareness is very important for social media users, especially teenagers. Many users become victims of cybercrime due to the lack of education about cybersecurity awareness. This case began with many complaints submitted by teenagers from SMP Negeri 2 Ngoro, one of whom was a victim of cybercrime on Instagram social media whose account was hijacked by unknown individuals. This also happens on WhatsApp social media where there are criminals who steal someone's identity to be used as a victim and commit fraudulent money transfers, credit and other fraud. The purpose of this study was to assess and ensure the level of cybersecurity awareness among the three most significant social media platforms in Indonesia, namely WhatsApp, Instagram, and TikTok. The Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) methods were used to analyze the online survey data set. The EFA results obtained were 6.67% insignificant in one of the factors contained in the knowledge variable and 93.33% EFA results stated significant. Meanwhile, the CFA calculation results obtained 80% results which were stated as Fit, indicating that the model accurately represented the data, 20% of the CFA calculation results stated Moderate Fit because they reflected values that were almost close to the fit value.